2020
DOI: 10.3390/rs12182902
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Satellite-Based and Reanalysis Precipitation Products in Detecting Long-Term Trends across Mainland China

Abstract: Despite numerous assessments of satellite-based and reanalysis precipitation across the globe, few studies have been conducted based on the precipitation linear trend (LT), particularly during daytime and nighttime, when there are different precipitation mechanisms. Herein, we first examine LTs for the whole day (LTwd), daytime (LTd), and nighttime (LTn) over mainland China (MC) in 2003–2017, with sub-daily observations from a dense rain gauge network. For MC and ten Water Resources Regions (WRRs), annual and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Further replacement of the underground ice by rainwaters is observed. However, this conclusion is based The assessment of accuracy of ERA5 P linear trend (Sun et al 2020) showed minor (about 1 mm/year) bias for northeastern part of China, that is near BC.…”
Section: Discussionmentioning
confidence: 93%
“…Further replacement of the underground ice by rainwaters is observed. However, this conclusion is based The assessment of accuracy of ERA5 P linear trend (Sun et al 2020) showed minor (about 1 mm/year) bias for northeastern part of China, that is near BC.…”
Section: Discussionmentioning
confidence: 93%
“…An improved topography is used in the MERRA‐2 model and can better capture the topography variations at different pressure levels over the TP (figures not shown). Many studies have used these reanalysis data and documented their reliability in climate studies (Reichle et al., 2017; S. Sun et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…For example, how good is the overall performance (e.g., Kling-Gupta Efficiency (KGE), which integrates impacts of bias, variability, and correlation coefficient on the overall performance [33]) of the PERSIANN-CDR in detecting extreme precipitation, and does this product reproduce linear trends of extreme precipitation? Particularly, the latter issue has been paid more and more attention in recent years (e.g., [34,35]) because the assessments regarding precipitation trends are the necessary foundation on which to accurately explore precipitation long term changes, especially for the regions with limited and even no observations. Therefore, this study aimed to: (1) comprehensively validate the PER-SIANN-CDR performance in detecting different extreme precipitation indices (e.g., the precipitation amount-, duration-, and intensity-based indices) over the HRB, based on four validation metrics (i.e., three continuous validation metrics and one overall performance metric), and (2) detect the PERSIANN-CDR capacity to reproduce linear trends of various extreme precipitation indices.…”
Section: Study Region and Datamentioning
confidence: 99%